Extracorporeal shock wave lithotripsy under intravenous sedation for treatment of urolithiasis. (2nd November 2018) - Reesink, Daan J.; Scheltema, J. M. W.; Barendrecht, M. M.; Boeken Kruger, A. E.; Jansonius, A.; Wiltink, J.; van der Windt, F.
Abstract: Background: In contrast to treatment with oral or intramuscular analgesics, extracorporeal shock wave lithotripsy (E.S.W.L.) can be performed with patients under sedation too. Besides the advantage of increased shock energy, patients tend to have more constant breathing excursions and are more idle during treatment, potentially increasing the stone-free ratio (S.F.R.) after treatment. Methods: This study presents the results of 310 patients who underwent 400 E.S.W.L. procedures under sedation, with a stationary lithotripter. Results: After one procedure, the S.F.R. was 54.8% (170/310). A second treatment was successful in 42.1% (32/76), a third treatment in 21.4% (3/14). Therefore, 66.1% (205/310) of patients eventually became stone-free. Kidney stones were successfully treated in 65.4% (161/246), ureteral stones in 68.8% (44/64) of cases. Patients with stones ≤15 mm were successfully treated in 67.4% (194/288), patients with stones >15 mm in 50% (11/22) of cases. Considering each procedure individually, 45.3% (181/400) of procedures were successful after 3 weeks. Extending follow-up to 3 months is important, since 26.7% of stones (24/90) eventually still disappeared, increasing S.F.R. to 51.3% after one procedure. Complications occurred after 5.5% E.S.W.L.-procedures. Conclusions: E.S.W.L. is a well-tolerated, non-invasive procedure that produces reasonable stone clearance of both upper and lower urinary tract calculi. Performing the procedure whilst patients are intravenously sedated results in an acceptable S.F.R. Strong selection based on unfavourable factors could increase the chance on successful treatment and spare patients a pointless procedure. However, considering E.S.W.L.'s elegant nature, sometimes a more tolerant approach seems justifiable.